2005
DOI: 10.1038/sj.leu.2403954
|View full text |Cite
|
Sign up to set email alerts
|

Translocation t(14;18) and gain of chromosome 18/BCL2: effects on BCL2 expression and apoptosis in B-cell non-Hodgkin's lymphomas

Abstract: Gain of chromosome 18q and translocation t(14;18) are] frequently found in B-cell non-Hodgkin's lymphomas (B-NHL). Increased BCL2 transcription and BCL2 protein expression have been suggested to be the result of the gain. We utilized FISH, PCR and array CGH to study BCL2 and chromosome 18 copy number changes and rearrangements in 93 cases of B-NHL. BCL2 protein was expressed in 475% of the tumor cells in 92% of the cases by immunohistochemistry. Gain of BCL2 was associated with a 25% increase in BCL2 expressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
24
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 40 publications
4
24
0
1
Order By: Relevance
“…Conversely, the C-terminal PEST domain is an important negative regulatory site required for ICN degradation, and loss of this region also leads to increased activity in the Notch-sensitive reporter assay, probably through stabilization of ICN. 3 All PEST domain mutations detected in our patients would lead to a similarly truncated protein. The probable functional consequence of the mutations identified in our study is supported by the loss of these mutations at remission and reappearance at relapse, which provides conclusive evidence that they are acquired and are specifically associated with the leukemic clone.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Conversely, the C-terminal PEST domain is an important negative regulatory site required for ICN degradation, and loss of this region also leads to increased activity in the Notch-sensitive reporter assay, probably through stabilization of ICN. 3 All PEST domain mutations detected in our patients would lead to a similarly truncated protein. The probable functional consequence of the mutations identified in our study is supported by the loss of these mutations at remission and reappearance at relapse, which provides conclusive evidence that they are acquired and are specifically associated with the leukemic clone.…”
mentioning
confidence: 99%
“…Functional analysis using a Notch-sensitive luciferase reporter assay has shown that leucine to proline point mutations in the HD domain lead to increased activity. 3 At least 10 of the 13 different HD domain mutations detected in our cohort are likely to result in an altered conformation, either through insertion of a proline residue, or loss or gain of amino acids. Conversely, the C-terminal PEST domain is an important negative regulatory site required for ICN degradation, and loss of this region also leads to increased activity in the Notch-sensitive reporter assay, probably through stabilization of ICN.…”
mentioning
confidence: 99%
See 3 more Smart Citations